Music rights unveiled a filmmaker's guide to music rights and licensing - Wentz, Brooke; Battaglia, Maryam (New York Routledge, Taylor & Francis Group, 2018)
"Music Rights Unveiled provides an inside look at the complex world of music rights for film and video, and includes step-by-step guidance to navigate these tricky waters. Authors Brook Wentz and Maryam Battaglia share their decades of expertise in this user-friendly guide, designed specifically with filmmakers and producers in mind. The book provides a brief history of the pricing of music in film, television and digital media markets, and explains the process by which music is licensed or acquired for films, highlighting pitfalls to avoid and strategies for success" -- From back cover.
Introduction: the Wild West, we meet again -- The law: for those respecting the law, we salute you. For the rebels, there is no such thing as free music -- Background and history: when synchs outshine soundtracks -- Music supervisors: every project can use a little music supervision -- Finding music: a community of composers, libraries and representatives -- The process of securing rights: a step-by-step guide to avoiding mistakes, because what you don't know can cost you -- Brand personality, identity and recognition: people rank music as more difficult to live without than sports, movies and newspapers -- Digital media and digital platforms: welcome to the digital era in all its forms -- For the artist: there is a musician in all of us -- Conclusion: parting words of encouragement.
Includes index.
Keywords: Music trade -- Law and legislation; Motion picture music -- Economic aspects; Copyright -- Music